Depressive symptoms and lack of social integration in relation to prognosis of CHD in middle-aged women - Horsten, M.; Mittleman, M. A.; Wamala, S. P.; Schenck-Gustafsson, K.; Orth-Gome´r, K. (European Heart Journal, 2000)
Several studies have reported that women with coronary heart disease have a poorer prognosis than men. Psychosocial factors, including social isolation and depressive symptoms have been suggested as a possible cause. However, little is known about these factors and their independent predictive value in women. Therefore, we investigated the prognostic impact of depression, lack of social integration and their interaction in the Stockholm Female Coronary Risk Study.Two hundred and ninety-two women patients aged 30 to 65 years and admitted for an acute coronary event between 1991 and 1994, were followed for 5 years from baseline assessments, which were performed between 3 and 6 months after admission. Lack of social integration and depressive symptoms, assessed at baseline by standardized questionnaires, were associated with recurrent events, including cardiovascular mortality, acute myocardial infarction and revascularization procedures (percutaneous transluminal coronary angioplasty and coronary artery bypass grafting). Adjusting for age, diagnosis at index event, symptoms of heart failure, diabetes mellitus, high density lipoprotein (HDL) cholesterol, history of hypertension, systolic blood pressure, smoking, sedentary lifestyle, body mass index, and severity of angina pectoris symptoms, the hazard ratio associated with low (lowest quartile) as compared to high social integration (upper quartile) was 2·3 (95% CI 1·2–4·5) and the hazard ratio associated with two or more (upper three quartiles) as compared to one or no depressive symptoms was 1·9 (95% CI 1·02–3·6).The presence of two or more depressive symptoms and lack of social integration independently predicted recurrent cardiac events in women with coronary heart disease. Women who were free of both these risk factors, had the best prognosis.
Keywords: Coronary disease, prognosis, women, depression, social support